2011
DOI: 10.1152/ajplung.00309.2010
|View full text |Cite
|
Sign up to set email alerts
|

Endocytic response of type I alveolar epithelial cells to hypertonic stress

Abstract: We present plasma membrane (PM) internalization responses of type I alveolar epithelial cells to a 50 mosmol/l increase in tonicity. Our research is motivated by interest in ATI repair, for which endocytic retrieval of PM appears to be critical. We validated pharmacological and molecular tools to dissect the endocytic machinery of these cells and used these tools to test the hypothesis that osmotic stress triggers a pathway-specific internalization of PM domains. Validation experiments confirmed the fluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 38 publications
1
37
0
Order By: Relevance
“…Because alveolar cells are not elastic, Oeckler et al (31) showed that plasma membrane-cytoskeletal adhesive interactions are important determinants of the cellular response to deforming stress. Caveolar endocytic response to transient actin remodeling following deformation of plasma membrane increases cell permeability in both alveolar (15,49) and endothelial cells (26) in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 98%
“…Because alveolar cells are not elastic, Oeckler et al (31) showed that plasma membrane-cytoskeletal adhesive interactions are important determinants of the cellular response to deforming stress. Caveolar endocytic response to transient actin remodeling following deformation of plasma membrane increases cell permeability in both alveolar (15,49) and endothelial cells (26) in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 98%
“…It is well described that most cells have the ability to repair their membranes; however, the underlying mechanisms remained incompletely understood (175). Recently, we learned that spatiotemporal actin remodeling and endocytic retrieval of plasma membrane are required for cells to repair the injured plasma membrane (77) and that the repair process requires Src-dependent calveolin-1 translocation to the plasma membrane to enhance caveolar endocytosis (115,250). Furthermore, the molecular mechanism of cell migration after injury, which is necessary to repair and cover sites of wounding, has been described to be mediated by inhibition of phosphatase and tensin homolog deleted on chromosome 10 (PTEN) in conjunction with activation of the Akt and ERK pathways decreasing cell stiffness, which results in larger cell deformations required for a more motile phenotype (159).…”
Section: Fibroproliferative Phase and Repair Alimentioning
confidence: 99%
“…Successful repair is facilitated by remodeling of the subcortical cytoskeleton in the vicinity of the PM lesion, by the reorientation of polar lipid heads at the wound margin, by the increase in PM fluidity consequent to a decrease in the adhesive interactions between inner PM leaflet lipids and cytoskeleton associated proteins, and by the trafficking of calcium-sensitive endomembranes in coordination with caveolar endocytosis (27,28). The effect of hypercapnia on cell repair appears to be pH dependent (29), in contrast to its effects on alveolar fluid clearance (12,13,30) and innate immunity (15,31).…”
Section: Effects Of Hypercapnia On Cell Membranesmentioning
confidence: 99%